(untitled) (PerCursos, 2023)
This article seeks to revisit and deepen contributions on the (re)production of space and housing from a Marxist-Lefebvrian and feminist perspective. The contributions and problematizations occur from two movements: 1) in the field of critical social theory, we seek to give centrality to the category of space production, reflecting how space has been consumed and (re)produced by the capitalist-racist-patriarchal system and what the consequences are in women’s daily lives; 2) in terms of emancipatory political practice, the daily experiences, struggles and resistance carried out by black women in search of guaranteeing the right to housing, through the reappropriation and construction of a differential, fair and dignified space, as well as the achievements incorporated in the housing and urban policies arising from this movement. From a methodological point of view, it is structured through bibliographic analysis, documentary sources, regulatory frameworks and social indicators disaggregated by gender and color/race, based on census data prepared by IBGE. As a result, it points out that the historical struggles of black women have allowed significant advances in housing and urban policies, however, with the capitalist-patriarchal-racist system intact and promoting constant dismantling of social rights, they are not able to face inequalities of gender, race and class in access to the right to housing and the city. Finally, in the face of successive attacks on the housing and urban sector to the detriment of a neoliberal counter-revolution project, it reinforces the urgency to retrace paths, strengthen the collective struggle in favor of claiming use as a principle and (re)appropriating the space through revolutionary and insurgent practices, so that the dialectic of possible-impossible is opened.